2018
DOI: 10.1017/s1368980018001453
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to exclusive breast-feeding in Indonesian hospitals: a qualitative study of early infant feeding practices

Abstract: Our study identified important barriers to early exclusive breast-feeding in Indonesian hospitals, finding that participants consistently reported multifaceted barriers to early exclusive breast-feeding. Future research should examine whether system-level interventions such the Baby-Friendly Hospital Initiative might improve rates of exclusive breast-feeding by improving breast-feeding education, reducing manufacturer influence, modifying existing infrastructure and providing tools needed for protocols and cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 25 publications
(35 reference statements)
2
20
0
4
Order By: Relevance
“…The promotion of infant formula also discourages EB practice in Indonesia [24]. The ease of infant formula access; aggressive marketing in retail outlets and the media; continued provision of formula samples and feeding supplies by health professionals; and lack of comprehensive understandings of optimal infant nutrition and feeding practices, are some of the reasons that families choose to use infant formula [13,24]. Violations of the Code by infant formula companies include incentivizing the provision of infant formula and feeding supplies by health professionals and retail outlets, and producing misleading advertisements and product labelling [25].…”
Section: Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The promotion of infant formula also discourages EB practice in Indonesia [24]. The ease of infant formula access; aggressive marketing in retail outlets and the media; continued provision of formula samples and feeding supplies by health professionals; and lack of comprehensive understandings of optimal infant nutrition and feeding practices, are some of the reasons that families choose to use infant formula [13,24]. Violations of the Code by infant formula companies include incentivizing the provision of infant formula and feeding supplies by health professionals and retail outlets, and producing misleading advertisements and product labelling [25].…”
Section: Previous Studiesmentioning
confidence: 99%
“…Bangka Belitung province had the highest rate of EB (56.7%), while West Nusa Tenggara province had the lowest prevalence (20.3%). Several recent studies have identified barriers to optimal breastfeeding practices in Indonesia, including: limited knowledge of breastfeeding among mothers and health workers; promotion of infant formula in retail outlets and by health workers; limited duration of maternity leave postpartum; and logistical challenges for women who return to the workforce after maternity leave [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hospital breastfeeding support was also implemented by following the Ten Steps to Successful Breastfeeding of Baby-Friendly Hospital Initiative (BFHI), including facilitating skin-to-skin contact or rooming-in practice in Indonesian public hospitals [6]. In spite of legislation and hospital efforts, mothers' perceptions of low milk supply and need for formula supplementation were the most common reasons for premature termination of breastfeeding in the immediate postpartum period and up to 6-months [7]. An in-depth understanding of mothers' perception of milk supply and its relation to breastfeeding practices is necessary and will be helpful for developing effective healthcare strategies to improve exclusive breastfeeding rates in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, mothers often adopt some unreliable signs, such as infant satiety cues or infant crying, as the primary indicator of insufficient milk supply [9], instead of assessing the infant's number of wet diapers and stools [10]. After delivery, mothers who perceive inadequate breast milk production tend to delay initiation of breastfeeding, wait until they believe their breast milk is 'adequate' [11], and may start to introduce unnecessary formula supplementation early [7]. Furthermore, studies suggest that approximately 25%~73% of mothers engage in early unnecessary cessation of breastfeeding due to perceived low milk production [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Beberapa peneliti telah menunjukkan hasil keefektifan intervensi pemberian dukungan menyusui, meskipun diantara penelitian tersebut masih terdapat bukti yang belum menunjukkan dampak positif intervensi. Oleh sebab itu, pengembangan multipel intervensi dilakukan meliputi dukungan menyusui co-parenting multifaset bagi ibu primipara multikultural (Abbass-Dick et al, 2015) (Flaherman et al, 2018), pemahaman yang salah mengenai kolostrum, dan penempatan neonatus terpisah dari ibu agar ibu dapat beristirahat paska operasi (Titaley, Loh, Prasetyo, Ariawan, & Shankar, 2014). Berdasarkan beberapa temuan tersebut, maka pendidikan kesehatan yang memadai terkait menyusui harus terus-menerus dilakukan agar ibu mendapat informasi yang benar dan dapat memperbaiki persepsi ibu dan keluarga.…”
Section: Variasi Intervensi Dukungan Menyusui Untuk Mempromosikan Pemunclassified